Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/00004872-200402000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol levels, blood pressure response to stress and incidence of stable hypertension in young subjects with high normal blood pressure

Abstract: These data suggest that subjects with high normal BP and elevated serum cholesterol might have an exaggerated cardiovascular response to stress and have an increased risk for stable hypertension that can be detected at young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…It is reported that elevated serum cholesterol levels, which were common in hyperlipidemic patients, might have an exaggerated cardiovascular response to stress (Borghi et al, 2004). It suggests that plasma cholesterol might be involved in blood pressure control and regulation In addition, the overwhelming evidence of both the cardioprotective and vasculoprotective profits of statin therapy and the continued discovery of actions of these agents independent of lipid lowering suggested that the modulation of blood pressure by statins may play a role in the hyperlipidemic-hypertensive patient (Chopra, Choksi, & Cavusoglu, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that elevated serum cholesterol levels, which were common in hyperlipidemic patients, might have an exaggerated cardiovascular response to stress (Borghi et al, 2004). It suggests that plasma cholesterol might be involved in blood pressure control and regulation In addition, the overwhelming evidence of both the cardioprotective and vasculoprotective profits of statin therapy and the continued discovery of actions of these agents independent of lipid lowering suggested that the modulation of blood pressure by statins may play a role in the hyperlipidemic-hypertensive patient (Chopra, Choksi, & Cavusoglu, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, heterogeneity was mostly due to differences in study populations, measures of exposure and outcome, losses and follow-up time. The effect of heterogeneity was partially overcome by the use of random effects models, subgroup analysis, a combination of effect by study and analysis of the impact of Menkes et al a 22 Markovitz et al d 26 Markovitz et al c 26 Markovitz et al b 26 Markovitz et al a 26 Carroll et al b 44 Carroll et al a 44 Matthews et al f 21 Matthews et al e 21 Matthews et al d 21 Matthews et al c 21 Matthews et al b 21 Matthews et al a 21 Borghi et al 43 Steptoe et al h 25 Steptoe et al g 25 Steptoe et al f 25 Steptoe et al e 25 Steptoe et al d 25 Steptoe et al c 25 Steptoe et al b 25 Steptoe Figure 3 Random effects model, odds ratio and 95% confi dence interval for the combined effect by study and the impact of the exclusion of each study.…”
Section: Discussionmentioning
confidence: 99%
“…Steptoe et al 25 Borghi et al 43 Matthews et al 21 Carroll et al 44 Markovitz et al 26 Menkes et al 22 Meta-analysis random-effects estimates (exponential form) Study ommited Table 3 Combined effect of psychological stress on the increase of the blood pressure in sub-groups of cohorts according to participants and study design. …”
Section: Discussionmentioning
confidence: 99%
“…The significant associations between MAP, NE levels, and their interactions in determining lipid levels are correlational and do not prove a causal link. For instance, some investigators suggest that having high normal BP and concomitant elevated serum cholesterol may lead to exaggerated cardiovascular responses to stress, due to endothelial dysfunction resulting from abnormalities of lipid metabolism [48]. Because of the sample size, conclusions pertaining to relationships observed between MAP and NE and specific lipids must be drawn with caution.…”
Section: Discussionmentioning
confidence: 99%